Intelligence Beliefs Predict Spatial Performance in Virtual Environments and Graphical Creativity Performance - Hong, Jon-Chao; Ye, Jian-Hong; Chen, Mei-Lien; Ye, Jhen-Ni; Kung, Ling-Wen (Frontiers in Psychology, 2021)
Although intelligence beliefs have been applied to explain the influence of cognition, behavior, and creativity, the research on creativity is still limited. Therefore, in order to effectively expand the understanding of the influence of intelligence beliefs on the creative performance of learners’ graphics, the implicit theories of intelligence were exploited as the basis of this study. Three hypothetical pathways were proposed to be explored, and a research model was validated. First- and second-year students from a technical high school in New Taipei City were invited to participate. There were 273 valid data (88.9% of complete data). Reliability and validity analyses were performed, as well as overall model fit analysis and research model validation, and descriptive statistical analysis of the learners’ performance in applying the operational virtual reality (VR). The results of this study showed that: (1) Incremental beliefs of aesthetic intelligence had a positive effect on spatial performance; (2) entity belief of spatial intelligence (EBSI) had a negative effect on spatial performance; and (3) spatial performance had a positive effect on graphical design performance. From the results, it is clear that design teachers can assess students’ implicit beliefs in the early stages of teaching to actively promote better spatial performance when students show high levels of entity beliefs.